A novel RUNX1 mutation with ANKRD26 dysregulation is related to thrombocytopenia in a sporadic form of myelodysplastic syndrome - Ferrari, Silvia; Regazzo, Daniela; Omenetto, Elisabetta; Scaroni, Carla; Semenzato, Gianpietro; Fabris, Fabrizio; Vianello, Fabrizio (Aging clinical and experimental research, 2021)
Aging is associated with a higher risk of developing malignant diseases, including myelodysplastic syndromes, clonal disorders characterised by chronic cytopenias (anaemia, neutropenia and thrombocytopenia) and abnormal cellular maturation. Myelodysplastic syndromes arising in older subjects are influenced by combinations of acquired somatic genetic lesions driving evolution from clonal haematopoiesis to myelodysplastic syndromes and from myelodysplastic syndromes to acute leukaemia. A different pattern of mutations has been identified in a small subset of myelodysplastic syndromes arising in young patients with familial syndromes. In particular, dysregulation of ANKRD26, RUNX1 and ETV6 genes plays a role in familial thrombocytopenia with predisposition to myelodysplastic syndromes and acute leukaemia. Whether these genes affect thrombopoiesis in sporadic myelodysplastic syndrome with thrombocytopenia is still undefined. Thirty-one myelodysplastic syndromes subjects and 27 controls subjects were investigated. Genomic DNA was used for mutation screening ( ETV6 , RUNX1 , 5′UTR ANKRD26 genes). Functional studies were performed in the MEG-01-akaryoblastic cell line. We found four novel variants of RUNX1 gene, all in elderly myelodysplastic syndromes subjects with thrombocytopenia. Functional studies of the variant p.Pro103Arg showed no changes in RUNX1 expression, but the variant was associated with deregulated high transcriptional activity of ANKRD26 in MEG-01 cells. RUNX1 variant p.Pro103Arg was also associated with increased viability and reduced apoptosis of MEG-01, as well as impaired platelet production. Our findings are consistent with dysregulation of ANKRD26 in RUNX1 haploinsufficiency. Lack of repression of ANKRD26 expression may contribute to thrombocytopenia of subjects with sporadic myelodysplastic syndromes.